Facile fabrication of metal‐organic frameworks with peroxidase‐like activity for the colorimetric detection of Alicyclobacillus acidoterrestris. Issue 1 (2nd December 2022) - Shi, Yiheng; Sun, Yuhan; Yue, Tianli; Yuan, Yahong
Abstract: Alicyclobacillus acidoterrestris ( A. acidoterrestris ), a kind of spore‐forming bacterium, could causes spoilage of fruit juices, which results in pecuniary losses to the industry. Unfortunately, the conventional methods used to identify this bacterium are laborious and complex. In this work, copper‐based metal‐organic frameworks (Cu‐MOFs) with intrinsic peroxidase‐like activity were fabricated by a self‐assembly method. Based on the properties of Cu‐MOFs, a colorimetric assay was developed for the detection of guaiacol, a characteristic metabolite of A. acidoterrestris and chromogenic substrate of peroxidase. Under optimal conditions, an excellent linear relationship was achieved over a range of guaiacol (0.01–0.4 mM), with a limit of detection (LOD) as low as 0.003 mM. This biosensor also showed a satisfactory sensing performance towards guaiacol, allowing the identification of A. acidoterrestris with high selectivity in a real sample. This present study provides a new perspective for the exploration of more sensitive and convenient methods for A. acidoterrestris detection. Abstract :